2022
DOI: 10.1002/er.8358
|View full text |Cite
|
Sign up to set email alerts
|

Plasticizer for controlling single‐walled carbon nanotube fibers and zincophilic sites of microfiber supercapacitor

Abstract: In the past few decades, single-walled carbon nanotube (SWCNT) fibers have been considered for various applications, from aerospace to electronics including flexible devices. Here, we report an effective way of controlling the viscosity of the liquid crystal SWCNT phases for fiber spinning. By applying Tris(hydroxymethyl)aminomethane (THA)-functionalization to single-walled carbon nanotubes (SWCNT_CONH), we enhanced the free volume of individual SWCNTs, which synergistically affected the formation of nematic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…You et al [46] reported an efficient method to control the viscosity of the liquid crystal SWCNT phase for fiber spinning. By functionalizing single-walled carbon nanotubes with tris(hydroxymethyl)aminomethane (THA), it was shown that as well-distributed zincophilic sites.…”
Section: D Carbon Current Collectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…You et al [46] reported an efficient method to control the viscosity of the liquid crystal SWCNT phase for fiber spinning. By functionalizing single-walled carbon nanotubes with tris(hydroxymethyl)aminomethane (THA), it was shown that as well-distributed zincophilic sites.…”
Section: D Carbon Current Collectorsmentioning
confidence: 99%
“…You et al [46] . reported an efficient method to control the viscosity of the liquid crystal SWCNT phase for fiber spinning.…”
Section: Three‐dimensional (3d) Current Collectorsmentioning
confidence: 99%